Lipid profile of spontaneously hypertensive rats after application of rhythmic extreme cryoeffect and conditioned medium of mesenchymal stromal cells - Kandybko, Igor; Syrotenko, Larysao (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):248